Monitoring of deiodinase deficiency based on transcriptomic responses in SH-SY5Y cells - Song, Mee; Song, Mi-Kyung; Choi, Han-Seam; Ryu, Jae-Chun (SPRINGER HEIDELBERG, 2013)
Iodothyronine deiodinase types I, II, and III (D1, D2, and D3, respectively), which constitute a family of selenoenzymes, activate and inactivate thyroid hormones through the removal of specific iodine moieties from thyroxine and its derivatives. These enzymes are important in the biological effects mediated by thyroid hormones. The expression of activating and inactivating deiodinases plays a critical role in a number of cell systems, including the neuronal system, during development as well as in adult vertebrates. To investigate deiodinase-disrupting chemicals based on transcriptomic responses, we examined differences in gene expression profiles between T3-treated and deiodinase-knockdown SH-SY5Y cells using microarray analysis and quantitative real-time RT-PCR. A total of 1,558 genes, consisting of 755 upregulated and 803 downregulated genes, were differentially expressed between the T3-treated and deiodinase-knockdown cells. The expression levels of 10 of these genes (ID2, ID3, CCL2, TBX3, TGOLN2, C1orf71, ZNF676, GULP1, KLF9, and ITGB5) were altered by deiodinase-disrupting chemicals (2,3,7,8-tetrachlorodibenzo-p-dioxin, polychlorinated biphenyls, propylthiouracil, iodoacetic acid, methylmercury, beta-estradiol, methimazole, 3-methylcholanthrene, aminotriazole, amiodarone, cadmium chloride, dimethoate, fenvalerate, octylmethoxycinnamate, iopanoic acid, methoxychlor, and 4-methylbenzylidene-camphor). These genes are potential biomarkers for detecting deiodinase deficiency and predicting their effects on thyroid hormone production.
Keywords: THYROID-HORMONE METABOLISM; IODOTHYRONINE 5-MONODEIODINASE ACTIVITY; GENE-EXPRESSION; IN-VITRO; IDENTIFICATION; INHIBITION; EXPOSURE; CADMIUM; BRAIN; LIVER